Das Haus Elis und das Haus Davids: Wie Gott sein Wort zurucknehmen kann - Loader, James Alfred (Hervormde teologiese studies, 2000)
The house of Eli and the house of David: how God can go back on God,s word. The interpretation of the rejection of Abiathar in terms of the Eli tradition offers an important indication of the intention of the Succession Narrative. The work does not only have a positive as well as a negative tendency as far as the Davidic dynasty is concerned, but the relationship between these two sides is one of conditionality. Therefore the critical aspect of the Succession Narrative contains both acceptance and warning. A sketch of the broader theological framework is given in which the interplay of God's love and his demand of obedience is understood in its historical context, including the redactional perspective.